THE APLICATION OF REVERSE TRANSCRIPTASE-POLYMERASE CHAIN REACTION FOR THE DIAGNOSIS OF CANINE DISTEMPER - Suartha, I Nyoman; Mahardika, I Gusti Ngurah Kade; Sri Candra Dewi, Ida Ayu; Dias Nursanty, Ni Ketut; L.S Kote, Yosaphat; Dwi Handayani, Anita; Ayu Suartini, I Gusti Agung (Jurnal Veteriner; Vol 9 No 1 (2008))
A study was conducted to apply reverse transcriptase-polymerase chain reaction (RT-PCR) technique for the confirmative diagnosis of canine distemper in dogs. Twenty mongreal dogs with clinical symptoms of canine distemper were used in this study. The viral RNA was isolated from nasal swab using Trizol® and transcribed into cDNA using random primers 5’ACAGGATTGCTGAGGACCTAT 3’. The cDNA was amplified in one step RT-PCR using primers 5’-ACAGGATTGCTGAGGACCTAT-3’ (forward) and 5’- CAAGATAACCATGTACGGTGC-3’ (backward). A single band of 300 bp which was specific for canine distemper virus CDV) was detected in fifteen out of twenty samples. It is therefore evident that confirmative diagnostics of canine distemper disease can be established with RT-PCR technique.
Keywords: diagnostics, canine distemper, RT-PCR